Associação entre implantes odontológicos e próteses parciais removíveis: revisão de literatura - Silva, Marcos Aurélio Bomfim da (2011)
Unilateral or bilateral distal-extension removable partial dentures present complex biomechanics. The movements in different directions, associated with the alveolar ridge shape and soft tissue resilience can lead to damaging forces on the supporting structures. The association between implants / removable partial denture aims to provide better mechanical and biological properties to the stomatognathic system. OBJECTIVE: The aim of this paper was to review the articles about the effect of implant support on distal extension removable partial dentures. LITERATURE REVIEW AND CONCLUSION: Studies have shown that this combination provides greater support, retention and stability to the prosthesis, thus limiting their approach movement toward supporting tissues and providing functional and psychological comfort to patients.